Allergic proctocolitis causing hematochezia in preterm twins - Karki, Bipin; Verma, Varsha; Shrestha, Ritesh; Joshi, Suchita Shrestha (Nepal Mediciti Medical Journal, 2020)
Allergic colitis due to cow’s milk or soy protein in commercially prepared infant formula or due to ingestion of breast-milk of mothers who are ingesting cow’s milk is a known cause of colitis occurring in infants. Allergic colitis can occur within days, weeks or months of birth and should be considered as a differential diagnosis in any infant presenting with hematochezia. Typically, there is a significant delay in the onset of milk allergy in premature infants compared to full term infants. We report a case of premature twin neonates who presented with profuse rectal bleeding during second week of life. The infants had been feeding expressed breast milk since birth and the nursing mother had been drinking cow’s milk. The infants had pneumatosis coli suggestive of inflammation of the colon while biochemical and hematological markers of inflammation were normal. Expressed breast milk was re-introduced after eliminating dairy from mother’s diet for 5 days. The infants were fed on mother’s milk and top up of hydrolyzed infant formula as required. Both the twins remained well.